Analysis of land use change and its relation to land potential and elephant habitat at Besitang Watershed, North Sumatra, Indonesia - WANDA KUSWANDA; AHMAD DANY SUNANDAR (Biodiversitas Journal of Biological Diversity, 2019)
Kuswanda W, Sunandar AD. 2019. Analysis of land use change and its relation to land potential and elephant habitat at Besitang Watershed, North Sumatra, Indonesia. Biodiversitas 20: 350-358. Land use change from forest into plantation at a watershed could be detrimental both for humans and wildlife. This study was aimed to analyze land use change and its impact on the habitat potential of Sumatran elephant (Elephas maximus sumatranus Temminck, 1857) in the upstream of Besitang Watershed located at Gunung Leuser National Park (GLNP), North Sumatra, Indonesia. The study was conducted from April to November 2015. Data collection was made through land cover map analysis, ground check and vegetation analysis using strip transect method. Land use change was analyzed using ArcView 3.2 software, species diversity was calculated using Shannon-Weiner formula and community evenness indices. Based on map delineation, total extent of Besitang Watershed is about 95,428 hectares. The analysis results showed that, in the past 25 years, about 15,989 hectares of land was changed from forests and farms to monoculture plantations. These changes have caused conflicts and threatened elephant population. As many as 168 species of plants were identified during vegetation analysis in the three study locations, namely Bukit Mas primary forest (88 species), Sekundur mixed secondary forest (91 species) and Halaban secondary forest (68 species). Average Importance Value Index (IVI) was below 40% which indicates that there are no dominant plant species. Tree density was between 360 and 497,5 individual/ha, sapling density was between 2,640 and 4,680 individual/ha, and density of seedling and understory plants was between 27,750 and 38,500 individual/ha. Species diversity index for each plant growth stage was relatively high (H’>3) and the similarity of plant species across locations was generally low (IS = <50%). Analysis of the correlation between land cover differences and habitat features showed statistically significant effects on species density and frequency. The highest effect of land cover change is on species density with the correlation reaching 94.5%. Forests in GLNP will be able to regenerate naturally to reach a stable state if there is no more land clearing to raise plantations.